Synthesis of a Novel Ce-bpdc for the Effective Removal of Fluoride from Aqueous Solution - Changqing Zhao; Yanwei Cui; Fang Fang; Si Ok Ryu; Jiarui Huang (Advances in Condensed Matter Physics)
Ce-1,1′-biphenyl-4,4′-dicarboxylic acid (Ce-bpdc), a novel type of metal organic framework, was synthesized and applied to remove excessive fluoride from water. The structure and morphology of Ce-bpdc were measured by X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The effects, such as saturated adsorption capacity, HCO3-, and pH, were investigated. The optimal pH value for fluoride adsorption was the range from 5 to 6. The coexisting bicarbonate anions have a little influence on fluoride removal. The fluoride adsorption over the Ce-bpdc adsorbent could reach its equilibrium in about 20 min. The Ce-bpdc coordination complex exhibited high binding capacity for fluoride ions. The maximum adsorption capacity calculated from Langmuir model was high up to 45.5 mg/g at 298 K (pH = 7.0) and the removal efficiency was greater than 80%. In order to investigate the mechanism of fluoride removal, various adsorption isotherms such as Langmuir and Freundlich were fitted. The experimental data revealed that the Langmuir isotherm gave a more satisfactory fit for fluoride removal. Finally, the tested results of ground water samples from three places, Yuefang, Jiangji, and Sanyi which exhibited high removal efficiency, also demonstrate the potential utility of the Ce-bpdc as an effective adsorbent.